Development and Validation of a Language Screening for Implementation in Pre-School Settings - Holzinger, Daniel; Weber, Christoph; Diendorfer, Bettina (Frontiers in Public Health, 2022)
Background: To prevent or mitigate long-lasting learning problems and emotional, behavioral and social-adaption difficulties associated with language disorders, good German language competence at school entry level is essential. Therefore, universal screening of children in their penultimate year of pre-school has been established in Upper Austria. So far, the screenings administered by speech and language pathologists to identify risk of language disorder (LD) were not based on standardized materials. Objective: To develop a screening instrument to identify increased risk of LD and to evaluate its validity and feasibility within the constraints of regular universal pre-school language screening. Design: A two-component screening instrument including direct assessment of expressive and receptive grammar was used in a sample of 374 children with German as their dominant language attending a public pre-school in their penultimate year (age 4-5 ½ years) in the state of Upper Austria. Assessment by use of standardized German language tests including a variety of linguistic domains was considered reference standard for diagnosing LD. Feasibility was assessed by a self-developed questionnaire completed by the administrators of the screening. Results: The combination of the expressive and receptive grammar scales demonstrated excellent accuracy (area under the curve score 0.928). A cut-off of 18 resulted in a failing rate of 21.8% and showed good sensitivity (84.2%) and specificity (85.3%). Acceptance by children and testers, time-economy and sustainability of the screening were mostly rated as high.